2012
DOI: 10.1017/s1366728912000065
|View full text |Cite
|
Sign up to set email alerts
|

Does language proficiency modulate oculomotor control? Evidence from Hindi–English bilinguals

Abstract: Though many previous studies have reported enhanced cognitive control in bilinguals, few have investigated if such control is modulated by language proficiency. Here, we examined the inhibitory control of high and low proficient Hindi–English bilinguals on an oculomotor Stroop task. Subjects were asked to make a saccade as fast as possible towards the appropriate colour patch among competitors and distractors suppressing an eye movement evoked by the meaning of the word. High proficient bilinguals quickly orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 56 publications
6
52
2
1
Order By: Relevance
“…The fact that we did not find any contribution of L2 proficiency in cognitive control advantages runs contradictory to findings from a few previous studies with children (Iluz-Cohen & ArmonLotem, 2013;Videsott et al, 2012) or young adults (Singh & Mishra, 2012Tse & Altarriba, 2012). This may be attributed to a few reasons.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fact that we did not find any contribution of L2 proficiency in cognitive control advantages runs contradictory to findings from a few previous studies with children (Iluz-Cohen & ArmonLotem, 2013;Videsott et al, 2012) or young adults (Singh & Mishra, 2012Tse & Altarriba, 2012). This may be attributed to a few reasons.…”
Section: Discussioncontrasting
confidence: 99%
“…Videsott, Della Rosa, Wiater, Franceschini, and Abutalebi (2012) suggest that proficiency levels in early multilingual children may play a crucial role in the development and enhancement of the alerting component of the attentional system in cognitive control. In other studies, language proficiency has been reported relevant to cognitive control performance on tasks requiring conflict resolution and goal maintenance (Tse & Altarriba, 2012), on tasks requiring inhibition (Singh & Mishra, 2012 and on tasks requiring inhibition and shifting (Iluz-Cohen & Armon-Lotem, 2013). However, language proficiency, as a complex construct (Hulstijn, 2012), generally does not reveal what degrees of proficiency may lead to better cognitive control.…”
mentioning
confidence: 94%
“…In inhibitory control specifically, bilinguals generally show smaller interference effects (the RT difference between incongruent and control trials) than monolinguals on both linguistic and non-linguistic conflict paradigms like the Stroop and Simon tasks [38][45], suggesting superior abilities at managing and resolving domain-general conflict. The smaller conflict effects for bilinguals when comparing incongruent and congruent trials is termed the bilingual ‘interference advantage’.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for these advantages is that bilinguals engage domain-general cognitive control mechanisms to manage the cognitive demands of bilingual language processing (e.g., Blumenfeld & Marian, 2011; Linck, Schwieter, & Sunderman, 2012; Pivneva, Palmer, & Titone, 2012; Prior & Gollan, 2011; Soveri, Rodriguez-Fornells, & Laine, 2011). Over time, growing experience with managing these demands might enhance nonlinguistic cognitive control abilities (e.g., Blumenfeld & Marian, 2013; Luk et al, 2011; Singh & Mishra, 2012). …”
Section: Introductionmentioning
confidence: 99%